Size matters: Zebrafish (Danio rerio) as a model to study toxicity of nanoplastics from cells to the whole organism. (1st January 2021) - Sendra, M.; Pereiro, P.; Yeste, M.P.; Mercado, L.; Figueras, A.; Novoa, B.
Abstract: The contamination of the aquatic environment by plastic nanoparticles is becoming a major concern due to their potential adverse effects in aquatic biota. Therefore, in-depth knowledge of their uptake, trafficking and effects at cellular and systemic levels is essential to understand their potential impacts for aquatic species. In this work, zebrafish ( Danio rerio ) was used as a model and our aims were: i) to determine the distribution, uptake, trafficking, degradation and genotoxicity of polystyrene (PS) NPs of different sizes in a zebrafish cell line; ii) to study PS NPs accumulation, migration of immune cells and genotoxicity in larvae exposed to PS NPs; and iii) to assess how PS NPs condition the survival of zebrafish larvae exposed to a pathogen and/or how they impact the resistance of an immunodeficient zebrafish. Our results revealed that the cellular distribution differed depending on the particle size: the 50 nm PS NPs were more homogeneously distributed in the cytoplasm and the 1 μM PS NPs more agglomerated. The main endocytic mechanisms for the uptake of NPs were dynamin-dependent internalization for the 50 nm NPs and phagocytosis for the 1 μm nanoparticles. In both cases, degradation in lysosomes was the main fate of the PS NPs, which generated alkalinisation and modified cathepsin genes expression. These effects at cellular level agree with the results in vivo, since lysosomal alkalization increases oxidative stress and vice versa. Nanoparticles mainly accumulated in the gut, where they triggered reactive oxygen species, decreased expression of the antioxidant gene catalase and induced migration of immune cells. Finally, although PS NPs did not induce mortality in wild-type larvae, immunodeficient and infected larvae had decreased survival upon exposure to PS NPs. This fact could be explained by the mechanical disruption and/or the oxidative damage caused by these NPs that increase their susceptibility to pathogens. Graphical abstract: Image 1 Highlights: The impact of PS NPs was studied at the cellular, molecular and systemic levels. The distribution and uptake of PS NPs in the ZF4 cell line were size dependent. PS NPs colocalized with lysosomes and raised the pH of these organelles. In vivo, PS NPs accumulated mainly in the gut and induced leukocyte migration. PS NPs decreased the survival of immunosuppressed or infected larvae.